Development of inclusive education in the Republic of Kazakhstan: an inside view (case of the Karaganda region) - Mamerkhanova, Zhanat; Sakayeva, Alfina; Akhmetkarimova, Kulbarshyn; Assakayeva, Dana; Bobrova, Valentina (Frontiers in Education, 2025)
In Kazakhstan, in the process of inclusive education, which ensures equal access to education for all children, taking into account their particular educational needs, priority is given to children who need special conditions. The number of such children in general education schools is steadily growing. However, the medical model continues to dominate in general education schools, and the state and public potentials for solving the problems of inclusion are insufficiently combined. The purpose of study is to evaluate a system of conditions for the introduction of inclusive education in general education schools in Kazakhstan (case of the Karaganda region). The system includes organizational and educational, scientific and methodological, staffing, regulatory and legal, financial, material and technical, and time-related conditions temporal conditions. The main research tool is the process approach to the quality management system. In the quality management system, the process of inclusive education is assessed in terms of meeting the educational needs of the child. The process approach allows us to design a model of the system of conditions for the functioning of the inclusive education process with a feedback mechanism. The research used methods of review and content analysis of open sources of government departments and organizations that determine the nature and regulate the content of the activities of general education schools in Kazakhstan in terms of inclusive education, as well as the collection and analysis of data from statistical reports of educational organizations of the Karaganda region. It is established that the existing process of inclusive education is a combination of general and special education processes. The established system of special conditions is insufficient, and work is underway to improve it. An attempt to create a qualitatively new “product” (inclusive education) using traditional approaches to general secondary education slows down this process. The lack of an inclusive approach to general secondary education hinders the development of inclusive education and the modernization of general secondary education in general. Focusing on meeting the special educational needs of all children, including those in need of special conditions, will significantly improve the quality of education in Kazakhstan’s general education schools.